The Effect of Tambsil Organic Fertilizer on The Growth And Results of Onion (Allium Ascalonicum L.) In Lowland - Bambang Wicaksono Hariyadi; Nurul Huda; Nurlina; Mahrus Ali; Elsi Wandik5 (Faculty of Agriculture, Merdeka University Surabaya, 2019)
This study aims to determine the effect of tambsil liquid organic fertilizer on the growth and yield of onion and find out the optimum dosage. This is a Randomized Block Design (RBD) consisting of five (5) treatments with three (3) replications and two (2) sample plants. Treatment in experimental plot was conducted randomly. Tambsil liquid organic fertilizer consists of six (6) doses including DT0 = without Tambsil liquid organic fertilizer (Control); DT1 = Tambsil liquid organic fertilizer 2.0 ml/liter of water/plant; DT2 = Tambsil liquid organic fertilizer 4.0 ml/liter of water/plant; DT3 = Tambsil liquid organic fertilizer 6.0 ml/liter of water/plant; DT4 = Tambsil liquid organic fertilizer 8.0 ml/liter of water/plant; DT5 = Tambsil liquid organic fertilizer 10.0 ml/liter of water/plant. The dose of Tambsil liquid organic fertilizer provides significant effect on the observation variables of plant length, number of leaves, number of bulbs and gross weight per clump of onion (Allium ascalonicum L.). The dose of Tambsil liquid organic fertilizer (DT4) 8.0 cc per liter of water always shows the highest growth and yield of onion (Allium ascalonicum L.) while statistically, BNT 5% is not significantly different from the treatment of Tambsil liquid organic fertilizer (DT3) 6.0 cc per liter of water (optimum dose) and (DT4) dose of 10.0 cc per liter of water.